Boost of cosmetic active ingredient penetration triggered and controlled by the delivery of kHz plasma jet on human skin explants - Vijayarangan, Vinodini; Dozias, Sébastien; Heusèle, Catherine; Jeanneton, Olivier; Nizard, Carine; Pichon, Chantal; Pouvesle, Jean Michel; Stancampiano, Augusto; Robert, Eric (Frontiers in Physics, 2023)
This work reports on the demonstration of the penetration of cosmetic active ingredients (caffeine and hyaluronic acid) in human skin explants following safe and controlled plasma jet exposure. First, temperature increase and immunohistochemistry in the stratum corneum and epidermis were characterized to check the safe delivery of plasma jet and to select two operation regimes at 1 and 20 kHz. Plasma exposure for tens of seconds is shown to induce transient modulations of the skin pH, the transepidermal water loss and the skin wettability revealing a reversible skin barrier function modulation. Then, it is demonstrated that plasma exposure significantly accelerates the penetration of active ingredients. The tuning of the plasma jet pulse repetition rate allows controlling the penetration kinetics. Such ex vivo results agree with previous in vitro experiments also exhibiting a transient permeabilization time window. A preliminary demonstration of human skin wettability modulation with a low power user-friendly dielectric barrier discharge setup is documented opening perspectives for plasma-based home cosmetic care device development. To the best of our knowledge, this work is one of the first demonstrations of safe and controlled plasma-assisted active ingredients skin penetration in the context of cosmetic applications.